A Mesoporous Nanoenzyme Derived from Metal–Organic Frameworks with Endogenous Oxygen Generation to Alleviate Tumor Hypoxia for Significantly Enhanced Photodynamic Therapy. Issue 27 (16th May 2019) - Wang, Dongdong; Wu, Huihui; Lim, Wei Qi; Phua, Soo Zeng Fiona; Xu, Pengping; Chen, Qianwang; Guo, Zhen; Zhao, Yanli
Abstract: Tumor hypoxia compromises the therapeutic efficiency of photodynamic therapy (PDT) as the local oxygen concentration plays an important role in the generation of cytotoxic singlet oxygen ( 1 O2 ). Herein, a versatile mesoporous nanoenzyme (NE) derived from metal–organic frameworks (MOFs) is presented for in situ generation of endogenous O2 to enhance the PDT efficacy under bioimaging guidance. The mesoporous NE is constructed by first coating a manganese‐based MOFs with mesoporous silica, followed by a facile annealing process under the ambient atmosphere. After removing the mesoporous silica shell and post‐modifying with polydopamine and poly(ethylene glycol) for improving the biocompatibility, the obtained mesoporous NE is loaded with chlorin e6 (Ce6), a commonly used photosensitizer in PDT, with a high loading capacity. Upon the O2 generation through the catalytic reaction between the catalytic amount NE and the endogenous H2 O2, the hypoxic tumor microenvironment is relieved. Thus, Ce6‐loaded NE serves as a H2 O2 ‐activated oxygen supplier to increase the local O2 concentration for significantly enhanced antitumor PDT efficacy in vitro and in vivo. In addition, the NE also shows T 2 ‐weighted magnetic resonance imaging ability for its in vivo tracking. This work presents an interesting biomedical use of MOF‐derived mesoporous NE as a multifunctional theranostic agent in cancer therapy. Abstract : A biocompatible mesoporous nanoenzyme derived from metal–organic frameworks is developed to alleviate tumor hypoxia. The nanoenzyme strongly catalyzes H2 O2 for endogenous O2 generation both in vitro and in vivo without any external activation, demonstrating enhanced photodynamic therapy efficacy in cancer treatment.